Difference between revisions of "008A Sample Final A, Question 1"

From Math Wiki
Jump to navigation Jump to search
 
Line 3: Line 3:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Foundations:  
+
!Foundations:  
 
|-
 
|-
 
|1) How would you find the inverse for a simpler function like <math>f(x) = 3x + 5</math>?
 
|1) How would you find the inverse for a simpler function like <math>f(x) = 3x + 5</math>?
Line 20: Line 20:
  
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 1: &nbsp;
+
!Step 1: &nbsp;
 
|-
 
|-
 
|We start by replacing f(x) with y.
 
|We start by replacing f(x) with y.
Line 28: Line 28:
  
 
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 2: &nbsp;
+
!Step 2: &nbsp;
 
|-
 
|-
 
|Now we swap x and y to get <math>x = \log_3(y + 3) - 1</math>
 
|Now we swap x and y to get <math>x = \log_3(y + 3) - 1</math>
Line 36: Line 36:
  
 
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 3: &nbsp;
+
!Step 3: &nbsp;
 
|-
 
|-
 
|From <math>x = \log_3(y + 3) - 1</math>, we add 1 to both sides to get
 
|From <math>x = \log_3(y + 3) - 1</math>, we add 1 to both sides to get
Line 54: Line 54:
  
 
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;"
! Final Answer: &nbsp;
+
!Final Answer: &nbsp;
 
|-
 
|-
 
|<math>f^{-1}(x) = 3^{x+1} - 3</math>
 
|<math>f^{-1}(x) = 3^{x+1} - 3</math>

Latest revision as of 22:56, 25 May 2015

Question: Find for


Foundations:  
1) How would you find the inverse for a simpler function like ?
2) How do you remove the in the following equation:
Answers:
1) you would replace f(x) by y, switch x and y, and finally solve for y.
2) By the definition of when we write the equation we mean y is the number such that


Solution:

Step 1:  
We start by replacing f(x) with y.
This leaves us with
Step 2:  
Now we swap x and y to get
In the next step we will solve for y.
Step 3:  
From , we add 1 to both sides to get
Now we will use the relation in Foundations 2) to swap the log for an exponential to get
.
Step 4:  
After subtracting 3 from both sides we get . Replacing y with we arrive at the final answer that
Final Answer:  

Return to Sample Exam